Prognostic Value of Lymph Node Evaluation in Stage II Small Bowel Adenocarcinoma: An Updated Analysis of Surveillance, Epidemiology, and End Results Database - Liu, Zhen; Liu, Kun; Gao, Jiale; Jing, Chao; Ma, Yanhong; Zheng, Shu; Shan, Jianzhen (Frontiers in Oncology, 2022)
Background: Due to the lack of large-scale clinical trials, the treatment strategies of small bowel adenocarcinoma (SBA) are controversial, especially for stage II patients. According to National Comprehensive Care Network (NCCN) guideline, few lymph nodes examined (<5 for duodenum or <8 for jejunal/ileal primary location) is one of the high-risk features for stage II patients, for whom adjuvant chemotherapy is recommended. This consensus is originally drawn from data in the Surveillance, Epidemiology, and End Results Database (SEER) between 1988 and 2010. However, the surgical modalities and chemotherapy strategies changed a lot after 2004 for SBA patients. The previous data may not represent a true picture of current therapeutics. Thus, we reanalyzed the SEER database and updated the cutoff point of lymph node (LN) numbers resected with respect to cancer-specific survival (CSS) using the latest SEER information. Methods: Patients diagnosed as stage II SBA and underwent curative surgery between 2004 and 2018 were extracted from the SEER database. CSS was calculated using the Kaplan-Meier method and compared by log-rank test. Maximum survival differences based on total LNs examined for duodenal and jejunoileal tumors were determined separately with the cut-point analysis and maximum log-rank χ2 statistic. A nomogram model was constructed based on the multivariate Cox analysis to predict 5‐ and 10‐year CSS, and was then validated with an internal cohort. Results: 935 stage II SBA patients met the inclusion criteria. The greatest difference in survival was found in patients who had removal of at least 5 LNs for duodenal and 12 LNs for jejunoileal tumor. Multivariate Cox analysis showed that age, T stage, histology grade, primary site and LNs numbers were independent prognostic factors for survival. The C index of nomogram model was 0.702 (95%CI: 0.663-0.741, p<0.001). Conclusions: The number of LNs harvested is an important prognostic factor for survival in stage II SBA patients. LN number examined <5 remains a high-risk factor for duodenum, but the cutoff point for jejunal/ileal tumors should rise from 8 to 12. Appropriate radical lymphadenectomy should be performed in stage II SBA surgery.